2011
DOI: 10.1111/j.1471-4159.2011.07180.x
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 regulates aggresome‐autophagy degradation pathway of α‐synuclein in response to MPP+‐induced stress

Abstract: Increasing evidence suggests that the ubiquitin-binding histone deacetylase-6 (HDAC6) plays an important role in the clearance of misfolded proteins by autophagy. In this study, we treated PC-12 cells over-expressing human mutant (A53T) a-synuclein (a-syn) and SH-SY5Y cells with MPP + . It was found that HDAC6 expression significantly increased and mainly colocalized with a-syn in the perinuclear region to form aggresome-like bodies. HDAC6 deficiency blocked the formation of aggresome-like bodies and interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 34 publications
1
50
0
Order By: Relevance
“…Mounting evidence suggests that although HDAC6 is not required for autophagy activation per se, it is critical for autophagosome-lysosome fusion [14,15] . Our recent findings showed that HDAC6 and dynein participated in the degradation of MPP + -induced misfolded α-synuclein aggregates by regulating the aggresome-autophagy pathway [16,17] .…”
Section: Mechanisms and Pharmacologic Targeting Of Autophagymentioning
confidence: 97%
“…Mounting evidence suggests that although HDAC6 is not required for autophagy activation per se, it is critical for autophagosome-lysosome fusion [14,15] . Our recent findings showed that HDAC6 and dynein participated in the degradation of MPP + -induced misfolded α-synuclein aggregates by regulating the aggresome-autophagy pathway [16,17] .…”
Section: Mechanisms and Pharmacologic Targeting Of Autophagymentioning
confidence: 97%
“…44 Recently, it was suggested that HDAC6-mediated protein degradation is protective in PD and dementia with Lewy bodies. 90 In this study, overexpression of mutant α-synuclein or 1-methyl-4-phenylpyridinium-induced neuronal stress significantly increases HDAC6 expression in PC-12 cells. 90 Likewise, HDAC6 inhibition reduces the autophagic response and the formation of Lewy bodies, followed by an impaired clearance of mutant α-synuclein.…”
Section: Pdmentioning
confidence: 58%
“…90 In this study, overexpression of mutant α-synuclein or 1-methyl-4-phenylpyridinium-induced neuronal stress significantly increases HDAC6 expression in PC-12 cells. 90 Likewise, HDAC6 inhibition reduces the autophagic response and the formation of Lewy bodies, followed by an impaired clearance of mutant α-synuclein. 90 The protective nature of HDAC6 was confirmed by a study in Drosophila in which the endogenous Hdac6 protects dopaminergic neurons against cytotoxic α-synuclein aggregates by stimulating aggresome-like inclusion formation.…”
Section: Pdmentioning
confidence: 58%
See 1 more Smart Citation
“…Similarly, Valproic acid, an inhibitor of histone deacetylase, counteracted the alteration of α-syn, the death of nigral neurons and the declined levels of striatal DA in the rotenone-treated rats [123]. Nevertheless, there were some evidences showing that the inhibition of HDAC6 exerted the detrimental effects including the accumulation of α-syn oligomers, the aggravated degeneration of nigrostriatal DA neurons and behavioral deficits [124][125][126]. In this line, HDAC or its inhibitors have been shown to exert effective roles in the inhibition of α-syn misfolding and treatment of PD.…”
Section: α-Synuclein Aggregation and Parkinson Diseasementioning
confidence: 99%